Exploring STEAM teaching in preschool using Fred Rogers approach - Zahiroh Awang; Nooraida Yakob; Aswati Hamzah; Mohd Mernan Talling (Institute of Advanced Engineering and Science, 2020)
The culture of Science, Technology, Engineering, Art and Mathematics (STEAM) teaching is still new among preschool teachers. Nevertheless, STEAM teaching is seen as challenging to be implemented if there is no clear guideline prepared by qualified experts. Therefore, a need analysis on STEAM teaching strategies ought to be conducted to ensure the implementation of STEAM teaching its related problems may be attended. This research aimed to explore experts’ perceptions about Fred Rogers’ STEAM as a STEAM teaching strategy approach as a considered method to be taught in preschools. This need analysis employed semi structured interviews with four experts. The obtained findings were categorized and analysed thematically. Five themes were identified: 1) features and needs of STEAM education, 2) inquiry-based learning 3) learning by doing activities, 4) interesting and systematic teaching strategies and 5) suitability with children’ development and practices. The research findings benefit preschool teachers in selecting and implementing STEAM teaching strategies based on experts’ opinion. Besides, it is anticipated to help teachers to conduct meaningful and effective STEAM teaching with preschool children.